Human Resources Management in the Public Hospital Case of the University Hospital Centre of Oran - Larbi, Ghrissi (European Journal of Economics and Business Studies, 2017)
:it would seem that the University Hospital Centre of Oran suffers from an insufficiency in the control ¶existing human resources and of an inadequacy enters the needs and the profiles ¶existing on the one hand, and that it would not have a true policy of management of ¶human resources which would enable him to benefit best from the resources ¶human available to take up the challenges of management and the development of ¶services provided to the patients.¶
Keywords: Human resources management, University hospital, Public sector, Recruitment, Skills assessment, Skills training.